2001
DOI: 10.1007/s101430100184
|View full text |Cite
|
Sign up to set email alerts
|

When should conservative treatment for lumbar disc herniation be ceased and surgery considered?

Abstract: Different authors recommend different time spans for conservative treatment before considering surgery in patients suffering from lumbar disc herniation. We analyzed the time of onset of symptoms such as pain, sensory deficit, and motor deficit in a surgically treated group in comparison to outcome after surgery in order to define a time threshold when surgical results deteriorate and operation should therefore be considered. General data, symptoms, signs, and neurological findings of 219 patients were preoper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
50
1
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(58 citation statements)
references
References 14 publications
4
50
1
3
Order By: Relevance
“…Whilst these variables have been identified as significant predictors of outcome in some retrospective studies (in which a limited number of ''readily available'' risk factors are typically examined), the majority of high quality prospective studies do not support a predictive role for them [15]. One of the risk factors commonly identified in previous studies, the duration of symptoms [11,19,21,24,29,32,33], was not shown to be a significant predictor in the present study. This may have been due to the paucity of acute patients in the study sample that would otherwise have provided a wider spectrum of values for this independent variable; a very high proportion of the whole sample (94%) were already ''chronic'' pain sufferers, according to the standard definition of >3 months pain.…”
Section: Discussioncontrasting
confidence: 65%
“…Whilst these variables have been identified as significant predictors of outcome in some retrospective studies (in which a limited number of ''readily available'' risk factors are typically examined), the majority of high quality prospective studies do not support a predictive role for them [15]. One of the risk factors commonly identified in previous studies, the duration of symptoms [11,19,21,24,29,32,33], was not shown to be a significant predictor in the present study. This may have been due to the paucity of acute patients in the study sample that would otherwise have provided a wider spectrum of values for this independent variable; a very high proportion of the whole sample (94%) were already ''chronic'' pain sufferers, according to the standard definition of >3 months pain.…”
Section: Discussioncontrasting
confidence: 65%
“…The typical presentation is a patient with predominant radicular leg pain on one side, with or without additional neurological disturbances; the amount of concomitant low back pain can vary greatly. The treatment is initially conservative [23], but if this fails, then decompression surgery of the affected nerve root is usually performed, and is associated with a generally favourable outcome [1,12,27].…”
Section: Introductionmentioning
confidence: 99%
“…A practical screening tool to identify patients at risk of long-term sick leave may further enhance cost-effectiveness [35]. In case of severe relapsing low back pain despite conservative treatment and when surgery is perceived as an invaluable option, intervention needs to be performed without undue delay [36][37][38].…”
Section: Resultsmentioning
confidence: 99%